Beyond liberal egalitarianism Marx and normative social theory in the twenty-first century - Smith, Tony 1951- (Brill, 2017)
Progressive theorists and activists insist that contemporary capitalism is deeply flawed from a normative point of view. However, most accept the liberal egalitarian thesis that the serious shortcomings of market societies (financial excess, inequality, and so on) could be overcome with proper political regulation. Building on Marx's legacy, Tony Smith argues in 'Beyond Liberal Egalitarianism' that advocates of this thesis (Rawls, Habermas, Stiglitz, et al.) lack an adequate concept of capital and the state. These theorists also fail to comprehend new developments in world history ensuring that the 'destructive' aspects of capitalism increasingly outweigh whatever 'creative' elements it might continue to possess. Smith concludes that a normative social theory adequate to the twenty-first century must explicitly and unequivocally embrace socialism
Includes bibliographical references and index
Keywords: Marx, Karl -- 1818-1883; Soziale Ungleichheit; Gleichheit; Egalitarismus; Marx, Karl 1818-1883 / Marx, Karl 1818-1883; Neoliberalism; Equality